PENGARUH MOTIVASI KERJA, PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT. WERSUT SEGUNI INDONESIA ROWOSARI, KENDAL - Efrat Parlinggoman; widiartanto Widiartanto (Universitas Diponegoro, 2018)
Human resource management currently views an employee who is in the company as a company asset. Although employees are seen as corporate assets, employees can not be obtained easily as other company assets in the form of goods. This is because it also requires a match between the qualifications that the company wants with qualifications possessed by job applicants. This match is required by the company, so that employees who work can help the company achieve its vision and mission. Vision and mission of a company, will mendaptkan with employee performance. Motivation work and career development have an influence on employee performance on employees of PT. Wersut Seguni Indonesia. This type of research is explanatory research, with sampling technique probability sampling is simple random sampling to 45 employees of PT. Wersut Seguni Indonesia. Measurement scale using Likert scale. In the analysis used factor analysis with the help of SPSS 20. Based on the results of the analysis, work motivation and career development variables have an influence on the performance of employees of PT. Wersut Seguni Indonesia. Career development variable has the biggest influence that is 11,40%, while work motivation variable have influence equal to 11,10%. The conclusion of this study indicates that the motivation of work and career development can affect the performance of employees of PT. Wersut Seguni Indonesia. The advice given is to increase the attention given to employees to be given training to improve soft skills and also rewarding employees who have good performance for the company.